Market Size and Factor Endowment: Explaining Comparative Advantage in Bilateral Trade by Differences in Income and Per Capita Income - Dieter Schumacher (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
Using a gravity-type explanation of international trade flows at the industry level, it is shown that the pattern of comparative advantage in terms of sectoral export/import ratios in bilateral trade can be explained by relative income and relative per capita income. Total income of a country is a proxy of its economic size and has a positive effect on comparative advantage in most manufacturing industries (home market effect). Per capita income represents the capital-labour endowment ratio and demand conditions. In sum, it has a positive effect in (human) capital-intensive industries and a negative effect in labour-intensive industries.
Keywords: F12; 330; Gravity model; comparative advantage; bilateral trade; home market effect; factor endowment; Internationale Wirtschaftsbeziehungen; Außenwirtschaft; Gravitationsmodell; Komparativer Kostenvorteil; Landesgröße; Volkseinkommen; Faktorproportionentheorem; Sozialprodukt; Schätzung; Theorie; Welt; Marktgröße